Analisis Tingkat Kematangan Manajemen Pelayanan Pembayaran Multiguna Pada Flatform Kredivo Menggunakan Framework ITIL Versi 3 - Ardiansyah, Reza; Titah; Sutabri, Tata (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
The level of service management maturity can lead to operational instability, inabilityIto respond quickly to market changes, and potential financial and reputational losses. This studyIaims to measureLthe level of maturityLin Kredivo service management. The data collection method is divided into 3, namely observation, interviews, andIquestionnaires. BasedLon the results of theLstudy, it isLknown that forLthe Event ManagementIvariable, theLaverage value of the maturity level is 3.32, which isIincluded in the levelL3 (defined) maturityIlevel.IFor the Incident ManagementIvariable, the average value of the maturity level is 3.52, which is includedIin the maturity levelI4 (managed). In the Problem ManagementLvariable, the average value of the maturity level is 3.30, which is included in the maturity level 3I(managed). For the Request Fulfillment variable, theIaverage value of the maturity level is 3.14, which isLincluded in the maturityLlevel 3 (defined). While in the Access Management variable, the maturity level value obtainedIis 3.40, which is included in the maturityIlevel 3 (defined). Thus, the overallIaverage value of theLmaturity level isI3.40, which isIincluded in the maturityIlevel of level 3L(defined). However, for the gap calculation, there is still a gap to reach the targer level, which is an average of 0.66. therefore recommendations are given so that Credivo can make the recommendations given as a reference in improving the maturity level of service management at Credivo. Keywords: Kredivo, Service Management, ITIL version 3